Beyond Western models: Rethinking employee engagement from non-Western empirical perspectives - Ganesh Prasad Niraula; Shreekrishna Kharel (Contemporary Research: An Interdisciplinary Academic Journal, 2026)
Employee engagement is an essential driver of organizational success, yet most frameworks are Western-centric and overlooked non-Western perspectives. This review examines how culturally responsive antecedents influence engagement in non-Western contexts. We conducted a systematic literature review of major databases such as Web of Science, Scopus, PsycINFO, and Google Scholar to find out the relevant literature. The main focus was to analyze theoretical models, measurement tools, and sectoral and geographical applications with a greater emphasis on methodological and regional diversity. The results reveal that employee engagement is consistently linked to performance, retention, and well-being across various contexts. However, the drivers of engagement differ significantly, with autonomy and personal resources in Western contexts, while in non-Western contexts, collectivism, hierarchical structures, and relational trust resources are the key drivers of engagement, indicating that cultural factors play crucial role in shaping engagement strategies. The studies heavily relied on a scale developed in Western contexts, this raised concerns about cultural validity, highlighting the need for locally developed scales. This review paper specifically enhances cross-cultural organizational psychology by integrating universal engagement principles with specific factors driven by local cultures. It focuses mainly on the necessity of creating indigenous measurement tools and suitable human resource development strategies for various contexts, offering understandings of engagement that are both globally and locally significant, how the same strategy could be significant for local and global context? particularly in addressing the unique challenges faced by organizations in different cultural settings.